2020
DOI: 10.1111/dth.14659
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photodynamic therapy for treatment of primary palmar hyperhidrosis

Abstract: Palmar hyperhidrosis represents a condition with a significant cosmetic and psychological burden. Various treatment modalities are available; however, searching for newer options to meet patients' needs and expectations is encouraged. The study aimed to evaluate the efficacy of photodynamic therapy (PDT) for treatment of primary palmar hyperhidrosis. Two different photosensitizers for PDT were evaluated: eosin Y, and methylene blue. The study focused on the clinical efficacy, patient's satisfaction, and the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Previous studies on hyperhidrosis treatment used liposomes, to enhance the drug delivery through palmar skin [ 11 , 15 ]. In this case study, we used transfersomes as it was proved that transfersomes were superior to liposomes in the dermal and transdermal delivery [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on hyperhidrosis treatment used liposomes, to enhance the drug delivery through palmar skin [ 11 , 15 ]. In this case study, we used transfersomes as it was proved that transfersomes were superior to liposomes in the dermal and transdermal delivery [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDT using EY as a PS (PDT-EY) was used previously for the treatment of both axillary [ 10 ] and palmar hyperhidrosis [ 11 ]. The results obtained from those studies revealed that the management of palmar hyperhidrosis was more difficult and took a longer time and higher number of sessions (8 sessions).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment for PPH comprises surgical and conservative traditional clinical therapies. Conservative clinical therapies contain skin application of antiperspirant agents, anticholinergic drugs, iontophoresis, Botulinum injections, photodynamic therapy and others (3)(4)(5)(6)(7). Regardless, all of these therapies have a temporary duration of effect, and some drugs may generate serious side effects if used for an extended period of time.…”
Section: Introductionmentioning
confidence: 99%